2019
DOI: 10.1002/jbio.201800286
|View full text |Cite
|
Sign up to set email alerts
|

The hemodynamic changes during cupping therapy monitored by using an optical sensor embedded cup

Abstract: Cupping therapy is one form of alternative medicine that is used widely across the world. Although the applications of cupping therapy including pain relief have a 1000‐year history, the therapeutic effect of cupping is still questionable due to a lack of scientific evidence. Therefore, in the present study, we embedded a near‐infrared spectroscopic sensor into a suction cup to monitor the hemodynamic changes on the treated site while the hemodynamics at the surrounding tissue of the cup was also simultaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This report [26] implied that the higher the internal pressure in the muscle, the greater the muscle stiffness. A recent study [27] examined the hemodynamic changes during cupping therapy and found that cupping therapy increased the blood volume and tissue oxygenation at the treatment site. Taking this evidence into consideration, it seems likely that dermal suction increases the blood flow and internal pressure in the muscle, which may increase muscle stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…This report [26] implied that the higher the internal pressure in the muscle, the greater the muscle stiffness. A recent study [27] examined the hemodynamic changes during cupping therapy and found that cupping therapy increased the blood volume and tissue oxygenation at the treatment site. Taking this evidence into consideration, it seems likely that dermal suction increases the blood flow and internal pressure in the muscle, which may increase muscle stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…The results from these two studies are quite consistent, suggesting improved blood circulation due to the cupping treatment. Similar measurements were repeated by Jae Gwan et al, who embedded an optical sensor within the therapy cup to monitor the hemodynamic changes during cupping [18]. They observed elevation of both deoxyhemoglobin and oxyhemoglobin at the cupping site but drop of both parameters at the surrounding positions, confirming cupping can increase the oxygen and blood supplement to cupping site.…”
Section: Introductionmentioning
confidence: 54%
“…Additionally, in pathological conditions, the application of this procedure is not limited to external diseases; is also widely used for internal diseases, to enhance healing through the purification of non-physiological fluids for improvement of systemic circulation, and for enhancing metabolism [3,10,11]. Recently, a number of studies characterized the principles and the efficacy of cupping therapy [11,12]. Moreover, since 1987, the National Health Insurance of Korea has approved cupping therapy, and the cupping therapy has been used for various conditions/diseases as a medical procedure [3].…”
Section: Discussionmentioning
confidence: 99%